Optimalisasi Potensi Pasar Lokal: Peluang Pemasaran UMKM dengan Media Digital - Surahmah Surahmah; Rahayu Mardikaningsih; Eli Masnawati; Muhammad Yusron Maulana El-Yunusi; Cilda Thesisa Ilmawan Dzinnur; Didit Darmawan; Novritsar Hasitongan Pakpahan (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
The increasingly rapid development of technology and information increases innovation and creative ideas, especially in economic activities. MSMEs as known Micro, Small, Medium Enterprise managed by individuals or groups, currently have to adapt to the application of technology and information in all industrial fields. The aim of this community service focuses on increasing the effectiveness of MSMEs marketing at the Makarya Binangunnn Market using online marketing methods. The method used is ABCD (Asset Based Community Development). The research results show that online marketing methods can effectively increase MSMEs income at the Makarya Binangun Market. The owner and the buyer also have benefits each other through easily access the market by online marketing media